Principles of Justice for Compensation for Land Procurement in Tamansari 11 Bandung City - Ali Said Hilabi; Mutiara Azura Mulyawan; Yuli Indrawati (Faculty of Law, Merdeka University Surabaya, 2022)
Land acquisition is an activity carried out by the government in providing land by providing appropriate and fair compensation to parties who Affected In land acquisition for development in the public interest, there are principles that must be met, one of which is the Principle of Justice, which is based on the explanation of Article 2 letter b of Law No. 2/2012 that the